1988
DOI: 10.1007/bf00254118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non-protected lower respiratory tract secretions and protected specimen brush samples in the diagnosis of pneumonia

Abstract: The aim of this prospective study was to compare the results obtained with the non-protected lower respiratory tract secretions samples (LRS) with the protected specimen brushes (PSB) performed through a fiberoptic bronchoscope in mechanically ventilated patients, when pneumonia was suspected. The diagnosis of pneumonia was ultimately made at the end of the hospitalisation, in a double-blind manner by 2 members of the medical staff not aware of the bacteriologic results of LRS and PSB. LRS and PSB were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…A negative EA culture would probably rule out pulmonary infection. Similar considerations were stated by Richard and colleagues (25). Finally, a recent publication by Middleton and associates (26), comparing EA, ACCU-CATH, PSB, and BAL for assessing VA pneumonia, showed a reasonable diagnostic value of Gram's stains and semi-quantitative cultures of EA.…”
Section: Discussionsupporting
confidence: 66%
“…A negative EA culture would probably rule out pulmonary infection. Similar considerations were stated by Richard and colleagues (25). Finally, a recent publication by Middleton and associates (26), comparing EA, ACCU-CATH, PSB, and BAL for assessing VA pneumonia, showed a reasonable diagnostic value of Gram's stains and semi-quantitative cultures of EA.…”
Section: Discussionsupporting
confidence: 66%
“…Two reports from our group [10,11] comparing qualitative cultures of endotracheal aspirates to quantitative cultures of protected specimen brush (PSB) and bronchoalveolar lavage (BAL) samples concluded that endotracheal aspiration was nonspecific (specificity 20-30%) in diagnosing ventilator-associated pneumonia. Some studies are consistent with these findings (12,15], although others have reported different results. For instance, KAsiAN et al [16] showed that endotracheal aspiration samples taken immediately after intubation were useful in 11 out of 14 children with a pulmonary infection.…”
Section: Non-invasive Techniquessupporting
confidence: 70%
“…Concomitant antimicrobial agents were employed by 42 (43%) ciprofloxacin-treated patients and 50 (47%) imipenem-treated patients in the efficacy-evaluable population. The concomitant antibacterial agents permitted by the protocol included vancomycin (27 patients) and metronidazole (11 patients) in the ciprofloxacin treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data suggest that the clinical criteria used to diagnose pneumonia lack specificity (2,13,42,45,46). Although strict diagnostic criteria were employed, newer invasive diagnostic methods, such as use of a protected specimen brush or bronchoalveolar lavage, were not routinely employed in this study.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation